FORMATION OF VISUAL AND INFORMATION CULTURE OF PRE-SERVICE MATHEMATICS AND COMPUTER SCIENCE TEACHERS: REFLEXIVE AND EVALUATIVE CRITERION - Drushlyak, Marina (Physical and Mathematical Education, 2021)
Formulation of the problem. Modern mathematics and computer science teacher must have a high level of visual and information culture, the structure of which necessarily includes a reflective component, which characterized by the ability to analyze, predict and reflect on their own professional activities to visualize educational material using computer visualization means, which provides professional self-development and self-improvement.Materials and methods. The study was based on scientific research of national and foreign scientists studying the training of pre-service mathematics and computer science teachers. To achieve this goal, the methods of the theoretical level of scientific knowledge were used: analysis of scientific literature, synthesis, formalization of scientific sources, description, comparison, and statistical methods: Pearson's test; Student's t-test.Results. To determine the level of formation of pre-service mathematics and computer science teachers’ visual and information culture, reflexive and evaluative criteria are distinguished, which is characterized by the ability to self-analyze, evaluate and reflexively interpret the results of their professional activities to implement computer visualization in education.Statistical calculations on the indicators of reflexive-evaluation criterion (critical attitude to the chosen computer visualization means, to the chosen of educational content visualization technology, awareness of typical mistakes in the introduction of information technology in the educational process (P1 "Ability to self-analysis"); updating and replenishing their own knowledge, skills and abilities in the field of information and mathematical disciplines and digital technologies (P2 "Ability to self-improvement") confirmed the statistical difference of the selected samples: for each pair of samples EG1 – CG and EG2 – CG for each indicator obtained  and statistical homogeneity for groups EG1 – EG2, because for each indicator obtained .Conclusions As a result of the implementation of the system of formation of pre-service mathematics and computer science teachers’ visual and information culture, students showed a critical attitude to the chosen computer visualization means in writing lesson plans or solving professional problems, desire to discuss ways to use computer visualization means in studying some topics of school mathematics, informatics with further analysis and correction of own professional activity, awareness of common mistakes in the use of information technology in the educational process, interest in replenishing their knowledge in the field of cognitive visualization by studying the experience of others, the development of scientific and methodological literature.
Keywords: visual and information culture; pre-service mathematics and computer science teachers; reflection; reflexive component of visual and information culture; reflexive and evaluative criterion